Dietary supplementation of betain to improve the growth and feed utilization in hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) juvenile - La Muhamad, Idul; Setiawati, Mia; Wiyoto, Wiyoto; Ekasari, Julie (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
Betaine plays some important roles in feed utilization and fish metabolism. The aim of this study was to evaluate the effect of dietary betaine supplementation on the growth performance and feed utilizationin hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). A completely randomized experimental design with four dietary levels of betaine, i.e.0.0%, 0.5%, 1.0%, and 2.0% in quadruplicate was done.Hybrid grouper juvenile obtained from Brackishwater Aquaculture Development Center, Situbondo, with an initial body length and body weight of 5.89 ± 0.05 cm and 2.86 ± 0.09 g, respectively was used as the tested animal. The fish was maintained in 60 cm x 40 cm x 40 cm aquaria with 75 L working capacity with individual recirculating system with a fish density of 15 fish/aquarium for 50 days. Experimental diet was provided to apparent satiation twice a day. The results of this study demonstrated that dietary betaine at a level of 0.5% resulted in higher feed utilization efficiency, protein and methionine retentions, and growth performance and lower ammonia excretion than those of the control (P<0.05). Higher antioxidative status was indicated by the lower malondialdehyde (MDA) in the liver of fish fed with betaine supplemented diets at levels of 1 - 2%. In conclusion, betaine supplementation of 0.5% could increase feed utilization efficiency and growth performance of hybdrid grouper. Keywods: Betaine, Hybrid Grouper, Growth Performance, Feed, Antioxidative Status ABSTRAK Betain memegang beberapa peranan penting dalam pemanfaatan pakan dan metabolisme pada ikan. Penelitian ini bertujuan untuk mengevaluasi pengaruh suplementasi betain pada pakan terhadap kinerja pertumbuhan dan pemanfaatan pakan pada juvenil ikan kerapu hybrid cantang (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). Penelitian menggunakan rancangan acak lengkap dengan empat perlakuan pakan dengan tingkat suplementasi betain yang berbeda, yaitu 0.0%, 0.5%, 1.0%, dan 2.0% dengan empat ulangan. Juvenil ikan kerapu cantang yang berasal dari Balai Pengembangan Budidaya Laut Situbondo dengan panjang dan bobot awal masing-masing 5.89 ± 0.05 cm and 2.86 ± 0.09 g digunakan sebagai hewan uji dalam penelitian ini. Ikan dipelihara dalam akuarium berukuran 60 cm x 40 cm x 40 cm dengan kapasitas 75L yang dilengkapi dengan sistem resirkulasi individu dengan kepadatan 15 ekor per akuarium selama 50 hari. Pakan uji diberikan hingga sekenyangnya dua kali sehari. Hasil penelitian ini menunjukkan bahwa suplementasi betain sebanyak 0.5% menghasilkan pemanfaatan pakan, retensi protein, retensi metionina, kinerja pertumbuhan dan ekskresi ammonia yang lebih baik daripada kontrol (P<0.05). Status antioksidasi yang lebih juga yang ditunjukkan dengan lebih rendahnya konsentrasi malondialdehid (MDA) pada hati ikan yang diberi pakan dengan suplementasi 1-2% betain. Berdasarkan hasil penelitian dapat disimpulkan bahwa suplementasi betain sebanyak 0.5% dapat meningkatkan efisiensi pemanfaatan pakan dan kinerja pertumbuhan ikan kerapu cantang.